On a Simple Survey Measure of Individual Risk Aversion - Joop Hartog; Ada Ferrer-i-Carbonell; Nicole Jonker (Tinbergen Institute, 2000)
We ask individuals for their reservation price of a specified lotteryand deduce their Arrow-Pratt measure of risk aversion.This allows direct testing of common hypotheses on risk attitudes inthree datasets. We find that risk aversion indeed fallswith income and wealth. Entrepreneurs are less risk averse thanemployees, civil servants are more risk averse thanprivate sector employees, and women are more risk averse than men. Weanalyze six different specifications of the lotteryquestion in a single data set and find quite consistent results. Weconclude that a simple lottery question is a promisingsurvey instrument to extract differences in risk attitudes amongindividuals.
Keywords: D81; C81; 330; Risikoaversion; Messung; Theorie; Brabant